The Sensitivity of British Weather to Ocean Tides. Issue 3 (10th February 2021) - Arnold, Alex K.; Lewis, Huw W.; Hyder, Patrick; Siddorn, John; O'Dea, Enda
Abstract: Tides in shelf seas greatly impact ocean mixing and temperature structure. Using a regional‐coupled ocean–atmosphere prediction system, at ocean coastal process and atmosphere convection permitting scales, we assess the influence of tides on British weather by comparing simulations with and without tides. In summer, when seasonal stratification is particularly sensitive to tides, the sea‐surface temperature is up to 6 K cooler in simulations with tidal mixing. Tides cool the air temperature over the sea by up to 3 K, and nearby land by up to 1.4 K. The mean air temperature across Great Britain land areas cools by 0.3 K with tides. Changes in near‐surface stability result in decreases in summer mean wind speeds over the ocean. A 6% reduction in summer precipitation is found with tides, consistent with cooler temperatures. This study has implications for climate projections since global‐coupled models typically do not include tides. Plain Language Summary: Ocean tides affect how heat is mixed through the shallow waters around the UK, which can affect the ocean surface temperature. We have used a new simulation approach which directly links detailed atmosphere and ocean models, to assess how the tidal influence on ocean temperatures affects the overlying atmosphere and the weather that develops further afield over land. We find tides have a stronger influence on the weather in summer than winter, and without tides around the UK, in summer, the average temperature would be warmer. Key Points: A regional atmosphere–ocean‐coupled model is used to assess the influence of ocean tides on the atmosphere In summer, when tides cool sea‐surface temperature, we find the mean air temperature and accumulated precipitation over land are decreased Smaller, but opposite, impacts of tides on British weather are found in winter